PEMBERDAYAAN SEBAGAI STRATEGI DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT DI KAWASAN PERBATASAN - Poppy Setiawati (SISI LAIN REALITA, 2016)
Empowerment is a successful strategy to improve the welfare of people in the region. Because of the ability it has. This concept views the community as the subject of development, not as a result of development, so that people can enjoy the real development. The synergy between government, community and private parties in empowerment is an important aspect in improving the welfare of people in the region. In the perspective of the science of defense, empowerment is one of the state defenses in the region. This condition supports the realization of the screen as a unified, sovereign and secure, united front porch of the Unitary State of the Republic of Indonesia.